Life and living conditions in north-west Arabia during the Bronze Age: first results from the bioarchaeological work at Qurayyah - Luciani, Marta; Binder, Michaela; Alsaud, Abdullah S. (Proceedings of the Seminar for Arabian Studies, 2018)
Transdisciplinary bioarchaeological and osteological research in Qurayyah, Saudi Arabia has begun with the aim of clarifying the agency behind the genesis of the so-called ’urban’ oases and the development of the population in the desert environment, beyond its incipient phase. Preliminary results have focused on Early to Middle Bronze Age burial buildings and one instance of a Late Bronze Age formal disposal of bodies. While these have revealed selective and specifie death-related behaviour, the pattern of the accompanying grave-goods (Red Burnished/Barbotine pottery, metal weapons, and beads made of materials ranging from amethyst to sandstone, shell, gold, and later, faience) find good comparisons with burials attested in the other main north Arabian oases: Taymāʾ, Khuraybah, and Madāʾin Ṣāliḥ. A series of radiometric determinations on a total of five different areas (Areas A-C, H, and K) have provided us with a varied but continued attestation of funerary remains ranging from the late third to the late first millennium cal Initial analysis of the skeletal human remains from Qurayyah has shown a series of pathological changes attesting to considerable negative environmental influences affecting the settlement’s inhabitants during this period. Combined with ongoing archaeological and palaeoenvironmental research, these results will form the basis of a study aimed at gaining a comprehensive insight into the living conditions and diachronic changes that occurred with reference to the dynamics of formation and development of ’urban’ oases in north-west Arabia.